Ocular Hydrogel Materials and Corresponding Methods of Anterior Segment Drug Delivery: A Review (International Journal of Engineering Materials and Manufacture, 2024)
Ocular conditions have historically proven difficult to treat. Topical eye drops are the primary method of anterior ocular drug delivery but have demonstrated low effectiveness as they require perpetual administration to achieve adequate doses of drug in the target tissue. This can lower patient compliance and increase the risk of side effects, such as systemic toxicity as most of the drug is absorbed through the eye’s natural clearance pathways. Considering this, further development of alternate anterior delivery methods has the potential to improve drug effectiveness, residence times, and bioavailability, as well as reduce systemic toxicity. To this end, the ongoing development of contact lenses, thermogels, nanoparticle delivery systems, as well as mucoadhesive and mucopenetrative properties are being explored. This paper will discuss these developments, as well as their implications in ocular treatment.